Knowledge and Motivation with Safe Behavior of Informal Sector Female Worker - Suryanto, Suryanto; Parmasari, Damairia Hayu (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
One of the informal sectors that absorbs labors in Indonesia is informal work in the household. This job can absorb workers but having health problems and safety risks if they do not apply safe behavior. Factors influence safe behavior are knowledge and motivation. This study is to determine the relationship of knowledge and motivation to safe behavior in the informal sector female workers. This research is cross-sectional quantitative observational design. The sample are 45 workers. The independent variables are knowledge and motivation. The dependent variable is safe behavior. The instrument is questionnaire. Research data is analyzed by chi-square. The result of the study showed no significant relationship between knowledge and safe behavior (p=0,496>0,05). Chi square analysis showed there is no significant relationship between motivation and safe behavior with p=0.545> 0.05. This study gives insignificant results, so the next researcher can discuss more factors that influence safe behavior with different research methods so that they can enrich new findings in the field of Occupational Safety and Health, both of which later give significant or insignificant results. Therefore, this research is important to be published. The conclusion from the study is no significant relationship between knowledge and motivation to safe behavior.